WANITA MALAM DALAM HEGEMONI SUPERSTRUKTURAL: PERSPEKTIF TEORI KRITIS (PENELITIAN TERHADAP GADIS MALAM MOTOR MATIK DI KOTA CIREBON) - Abdul Karim (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
: Cirebon is the “heart” of the city for several districts of Indramayu, Majalengka and Kuningan. It got the nickname as a city guardian, with the mandate of Sunan  Gunung  Jati, “Ingsun titip tajug lan fakir Miskin”. But when night falls, the identity of religious life of the town mayor as if suddenly changed, especially on Friday night. At one particular congregation, pilgrims flock to the Tomb guardian, but the other party actually visited the place dimly lit stalls (night cafe)  inhabited by girls night. This study will answer questions about  how  the hegemony of the superstructure of the girl automatic motor  night in the city of Cirebon? What  public  opinion  against  the social status  of girls night? What reasons are causing  the girls night hung in night cafe? By doing so, is there  any indication of gender equality  that they want?  What  is done  by allowing  the  establishment apparatus dimly lit stalls and jasmine is a form of superstructural hegemony. This is an indication that they are officials with direct and  intentional nurture girls selling themselves for a night at the venue.  Thus, the authorities will benefit  from what they do.